Implementation of Lebong Regent Regulation Number 32 of 2014 Regarding the Preparation of Public Service Standards - Yohanes Susanto; Shinta Wiji Rahayu (Ilomata International Journal of Social Science, 2021)
This research will discuss about how the efforts of the Lebong Regency Government in implementing the Lebong Regent Regulation No. 32 of 2014 concerning Preparation of Public Service Standards Considering that in order to increase efficiency, effectiveness, transparency and accountability of government administration and public services, it is necessary to have public service standards in regional work units / work units within Lebong Regency. In this research, the method used is juridical normative, which wants to study or analyze the forms of implementation of the Lebong Regent's regulation which are regulated in Regulation Number 32 of 2014, then analyze the implementation based on the legal basis that governs the law, then find suitability. Among the forms of implementation that are regulated by the legal ideals of making them. The main focus of this research is the extent to which the Lebong District Government's implementation process is, and what are the strategies used in implementing the implementation. Based on this research, the results obtained show that implementation efforts and strategies are used to increase efficiency, effectiveness, transparency and accountability of government administration and still refer to the vision and mission of the Lebong Regency Government.